Relationship between Company Size, EPS, Leverage and Financial Performance of Pharmaceutical Companies on the IDX - Dina Andini; Yumi Sri Andriati (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This research aims to determine the influence of company size, EPS, and leverage on the financial performance of manufacturing industry companies in the pharmaceutical sub-sector listed on the IDX. Design/Methodology/Approach – This research uses secondary data from financial reports of pharmaceutical companies on the Indonesia Stock Exchange in 2018 - 2022. The sample used was 8 companies with sample selection using purposive sampling technique. The analysis used is multiple linear regression with the Eviews 9.0 analysis tool. Findings – The results of this study show that Company Size has no effect on financial performance, EPS has a significant effect on financial performance, Leverage has no effect on financial performance. Conclusions and Implications - Based on the results, it is found that company size has no effect on financial performance, while EPS has a positive effect on financial performance and leverage has a negative effect on financial performance. Pharmaceutical sector companies listed on the IDX can increase EPS and reduce leverage to improve financial performance.